Moving Through the Space of the Picture and the Page : The Photobook as an Artistic and Architectural Medium - Vanthuyne, Stefan (S.l. : Art Paper Editions, 2022)
Guns, Tine ; Braeckman, Dirk ; Martens, Els ; Pinckers, Max ; Delbrouck, Vincent ; Konrad, Aglaia
boek